Development of a hybrid 3D virtual-reality UDK-based simulator for UAV applications - Li, Jue Kun. (2013)
The unmanned aerial vehicle (UAV) is an aircraft with no pilot onboard. UAVs can be remote controlled aircraft or can fly autonomously based on pre-programmed flight plans or more complex dynamic automation systems. Applications for UAVs are rapidly increasing in number in both the military and the civilian fields. For example, search and rescue missions in remote areas where access is hampered by mountains, vast land areas without road networks or areas afflicted by natural disaster may be aided and improved by autonomous UAV systems. In this final year project, attempts have been made to simulate some UAV applications in the virtual-reality environment built from the Unreal Development Kit (UDK), which is a popular game development tool. Two UAV models have been constructed and tested in the UDK environment, which shows excellent resemblance to the real world. In addition, the A* path planning algorithms have been applied to the quadcopter for search missions under different situations. The results have shown that the search mission can be well accomplished and still improvements can be made in the future works.